Study on cutting force model in ultrasonic vibration assisted side grinding of zirconia ceramics. (May 2016) - Xiao, Xingzhi; Zheng, Kan; Liao, Wenhe; Meng, Heng
Abstract: Ultrasonic vibration assisted side grinding (UVASG) has outstanding performance in machining hard-and-brittle materials, such as ceramics. The cutting force is the key factor that affects the machined surface/subsurface quality, which has been investigated both experimentally and theoretically. However, the combined effect of both ductile removal and brittle fracture removal on cutting force model in UVASG of ceramics has not been reported yet. In this study, a theoretical cutting force model is proposed with the consideration of the ductile-to-brittle transition removal mechanism in UVASG of ceramics. The critical cutting depth of ductile-to-brittle transition has been determined experimentally to distinguish the ductile region and brittle region. Besides, the average cutting depths have been derived for the modeling of the cutting forces in ductile and brittle region, respectively. Then the number of active diamond grits has been presented for the development of the final cutting force model. The parameter K is introduced to represent the influence of overlapping and intersection between different diamond grits. In addition, the relationship between cutting force and input variables has been revealed through the model. Finally, the pilot experiments are conducted to verify the theoretical model. The experimental results are consistent well with the model predictions. Therefore, the theoretical model can be applied to evaluate the cutting force, and it can provide better understanding of the effects of ductile removal and brittle fracture removal on the cutting force during UVASG of ceramics. Abstract : Highlights: Combined effect of ductile and brittle removal on the cutting force is considered. The number of active diamond grits has been calculated. The model focuses on the side grinding, which is ignored in previous study. It proposes a novel method for the modeling of cutting force in UVASG of ceramics.